Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd005342.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant platinum-based chemotherapy for early stage cervical cancer

Abstract: Background This is an updated version of the original Cochrane review published in The Cochrane Library 2009, Issue 3. Most women with early cervical cancer (stages I to IIA) are cured with surgery or radiotherapy, or both. We performed this review originally because it was unclear whether cisplatin-based chemotherapy after surgery, radiotherapy or both, in women with early stage disease with risk factors for recurrence, was associated with additional survival benefits or risks. Objectives To evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…Cervical carcinoma development begins with the infection of the cervical epithelium by high-risk human papillomaviruses (hr-HPVs) [3-5]. Although cervical cancer can be detected in its early stages by HPV testing and Papanicolaou (Pap) smear screening and successfully eradicated through surgery, curative treatments do not yet exist for advanced, recurrent or metastatic disease [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…Cervical carcinoma development begins with the infection of the cervical epithelium by high-risk human papillomaviruses (hr-HPVs) [3-5]. Although cervical cancer can be detected in its early stages by HPV testing and Papanicolaou (Pap) smear screening and successfully eradicated through surgery, curative treatments do not yet exist for advanced, recurrent or metastatic disease [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…Per the National Comprehensive Cancer Network guidelines, use of pelvic irradiation with concurrent administration of weekly chemotherapy (CCRT) is recommended as adjuvant therapy for node‐positive early‐stage cervical cancer . However, a recent meta‐analysis showed that CCRT is associated with increased risk of severe toxicity . Owing to this toxicity profile which is mostly related to radiotherapy, systemic chemotherapy has been considered as an alternative treatment option for adjuvant therapy after primary surgical treatment for this high‐risk group.…”
mentioning
confidence: 99%
“…7 However, a recent meta-analysis showed that CCRT is associated with increased risk of severe toxicity. 8 Owing to this toxicity profile which is mostly related to radiotherapy, systemic chemotherapy has been considered as an alternative treatment option for adjuvant therapy after primary surgical treatment for this high-risk group. While some studies suggested a possible utility of systemic chemotherapy, others concluded that systemic chemotherapy does not improve survival outcome.…”
mentioning
confidence: 99%
“…2 The prognostic factors affecting the survival of patients with cervical cancer mainly include the International Federation of Obstetricians and Gynecologists (FIGO) tumor staging system, lymph node (LN) status, tumor size, and depth of invasion. 3,4 Except the stage of disease, other variables can only be evaluated after surgery. Therefore, a noninvasive and readily accessible preoperative test to estimate survival probability and prognosis in cervical cancer is necessary.…”
mentioning
confidence: 99%